G291(P) Unintentional childhood injuries in sub saharan africa – a focussed literature review 2009–2015. (12th March 2018) - Eder, B; Magnus, D
Abstract : Aims: Childhood injury disproportionately affects children in low and middle-income countries and Sub Saharan Africa has the highest death rate in the world from injury. Given the burden of childhood injury in Sub Saharan Africa the allocation of resources for public health interventions to address this problem are inadequate. This focussed literature review aimed to describe the burden of childhood injury in Sub Saharan Africa and to explore the extent to which trauma registries or injury databases are being used by focussing on research conducted following the Report on Child Injury Prevention. Methods: A search protocol was designed using the key terms 'child* or paediatric or paediatric' AND 'injur* or trauma' AND 'unintentional or accident*.' The literature was reviewed for all studies in Sub Saharan Africa as defined by the United Nations. The databases Medline, Pubmed and Web of Science were searched for papers in the English Language that have been published since 2009. Twenty eight papers were identified for full text review and thirteen papers met the inclusion criteria. Data were extracted from the papers and common themes discussed. Results: Six countries out of the fifty one in Sub Saharan Africa had published papers on childhood unintentional injury since 2009. A large degree of heterogeneity existed between the studies. There were significant differences in the proportion of unintentional injuries due to either falls or road traffic incidents depending on the location of the study. Burns were found to be most common in children under the age of 5 whilst boys in all studies were more at risk of injury. Children were more likely to be injured at home or on the streets as opposed to school. Conclusion: Childhood unintentional injury in Sub Saharan Africa is under researched. Greater efforts need to be made to carry out research at a local level in order for public health interventions to produce the most benefit. The widespread implementation of trauma registries will help this process.